Analysis of the effect of net income and operating cash flows on cash dividends in LQ 45 index companies - Ardiansyah, Ardiansyah (Universitas Muhammadiyah Pontianak, 2018)
The research is empirical studies aimed at to analyse the influence of net profit and operating cash flow toward dividends cash to LQ-45 companies that listed on the Indonesia Stock Exchange. The independent variable in the research was net profit and operating cash flow with dividend cash as the dependent variable.This research is research with the design causal which is research aimed to analyse the relationship between variable research. The method for the took sample that used in this research is purposive sampling and obtained 28 company as a sample. The way of analysis is multiple regression with test the classical assumption and hypothesis test.This research concludes that both of two independent variables have a positive influence toward cash dividend in simultan, but in individual net profit have positive significant toward cash dividend, whereas operating cash flow is not influence cash dividend.